ASSESSING FUTURE SPATIAL DISTRIBUTION OF THE SEASONAL RAINFALL IN BINTAN ISLANSD USING THE DOWNSCALED CORDEX-SEA MODELS - Eko Kusratmoko; Muhamad Rahman Djuwansah; Faiz Rohman Fajary; Widya Ningrum; Ida Narulita; Dwita Sutjiningsih (International Journal of Remote Sensing and Earth Sciences, 2024)
Sustainable water resource management must consider climate change to minimize climate disasters. The water resources of Bintan island are limited, although rainfall is quite high, but the small catchment area and the component rocks of the island of Bintan have low water retention capacity. Currently, Bintan Island is experiencing an increase in water needs due to population growth and economic activities. Therefore, understanding changes in seasonal rainfall in the future is important on this island. This paper aims to study the chances of future seasonal rainfall variability using long-term projection climate modeling. Currently, a high-resolution climate model is available for historical and future periods, namely CORDEX-SEA for the Southeast Asia region. Because the study area is a small island with an area of around 1170 km2, the resolution of the CORDEX-SEA projection climate model data is insufficient. This study uses a statistical downscaling method with quantile mapping to detail the spatial resolution. The results of the analysis show that rainfall on Bintan Island is likely to change in the future due to climate change. Rainfall in Bintan Island in the future will likely be below normal rainfall in all seasons, except in the northern part of Bintan in the SON season. The greatest posibility of rainfall is below normal rainfall in the JJA season. The analysis results show that the eastern part of Bintan Island is a suitable area to build a water reservoir for managing water shortages in Bintan island caused by potentially decreasing rainfall in the future.